Short-video platform use and adolescent body dissatisfaction: The mediating role of body image comparison and the moderating role of sex - Liheng Fan; Yanan Zuo; Ke Yang (Acta Psychologica)
With the rising popularity of short-video platforms as a new form of media, an increasing number of adolescents are using these platforms. Unlike traditional social media, short-video platforms rely heavily on visual communication. Although social media is known to contribute to heightened body dissatisfaction, and while these highly visual media platforms may further exacerbate body dissatisfaction, particularly among adolescents, empirical research on this issue has not kept pace with their rapid adoption. Given the importance of body awareness in adolescent development, this study investigated the mechanisms underlying the relationship between short-video platform use and body dissatisfaction among adolescents. It also examined the moderating effect of sex in this relationship. A total of 795 adolescents (mean age = 14.66 ± 1.39 years, 451 girls) from China participated in a questionnaire survey. The findings revealed that (1) there was a significant positive correlation between short-video platform use, body image comparison, and body dissatisfaction; (2) body image comparison mediated the relationship between short-video platform use and body dissatisfaction; and (3) the mediating effect of body image comparison was moderated by sex, with the effect being more pronounced for girls than for boys. These findings not only contribute to existing theoretical frameworks but also provide empirical insights to support interventions aimed at improving body satisfaction among adolescents.